Kolaborasi Harmonis: Moderasi Beragama Mahasiswa Kkn Uinfas Dan Masyarakat Hindu Melalui Kegiatan Sosial Di Desa Talang Benuang - Topati Milta Biansyah; Zeta Kaisyah Maharani; Melsa Oktavia; Faula Ayustina; Holin Agustin; Yezi Yolita; Titi Aulia; Elva Indriani; Fika Puspita Sari; Putra Adi Pratama; M. Ilham Gilang (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This article discusses the harmonious collaboration between students of the Fatmawati Sukarno Islamic University (Uinfas) Bengkulu and the Hindu community in Talang Benuang Village. The main focus of this research is religious moderation created through various social activities that involve direct interaction between students and the community. Through programs such as environmental activities, KKN students not only contribute to the development of the village but also build effective communication bridges between two communities with different cultural and religious backgrounds. This research shows that this collaboration has succeeded in creating a sense of mutual respect and understanding, which in turn encourages religious moderation in daily life.